Quantitative assessment of the effects of biochar amendment on photosynthetic carbon assimilation and dynamics in a rice–soil system. Issue 3 (19th August 2021) - Liu, Zhiwei; Wu, Xiulan; Li, Shixian; Liu, Wei; Bian, Rongjun; Zhang, Xuhui; Zheng, Jufeng; Drosos, Marios; Li, Lianqing; Pan, Genxing
Summary: Biochar amendment has been proposed as a promising means to increase carbon (C) sequestration and simultaneously benefit plant productivity. However, quantifying the assimilation and dynamics of photosynthetic C in plant–soil systems under biochar addition remains elusive. This study established two experimental factors involving biochar addition and nitrogen (N) fertilization to quantitatively assess the effect of biochar on photosynthetic C fate in a rice plant–soil system. The rice plants and soil samples were collected and analyzed after 6‐h pulse labeling with 13 CO2 at the tillering, jointing, heading and ripening stages. Biochar did not affect the proportions of photoassimilated carbon‐13 ( 13 C) allocations in plant–soil systems. Nevertheless, biochar enhanced the 13 C contents in the shoot, root, and soil pools, especially when combined with N fertilization, and biochar increased the cumulative assimilated 13 C contents in the shoot, root, and soil pools by 23%, 14% and 20%, respectively, throughout the whole growth stage. Moreover, biochar addition significantly enhanced the N use efficiency (NUE) by c. 23% at the heading and ripening stages. In summary, biochar increases the content of photoassimilated C in plant–soil systems by improving plant productivity via enhancing NUE, thus resulting in a higher soil C sequestration potential.